Cardiospecific knockout of αE-catenin leads to violation of the neonatal cardiomyocytes maturation via β-catenin and Yap signaling - Balatskyi, V.V.; Ruban, T.P.; Macewicz, L.L.; Piven, O.O. (Вiopolymers and Cell, 2017)
Aim. To study the αE-catenin gene function in neonatal cardiomyocytes proliferation and matura-tion. Methods. Conditional knockout approach, histological (H&E and acridine orange staining) and molecular genetics (qPCR) methods were used. Result. The hetero- and homozygous embry-onic cardiospecific knockout of αE-catenin is associated with an increased level of neonatal car-diomyocytes proliferation and a decreased binucleated cells frequency. Knockout of αE-catenin leads to up-regulation of the β-catenin- and Yap-target genes expression (Axin2, c-Myc, Tcf-4, CyclinD1, Ctgf and Tnfrsf1b). Conclusion. αE-catenin is involved in the regulation of prolifera-tion and maturation of neonatal cardiomyocytes via modulation of the activity of β-catenin- and Yap-dependent transcription.